Pengaruh Faktor Lingkungan dan Peran Orang Tua Terhadap Pemilihan Menu Makan Ibu Menyusui di Wilayah Kerja Puskesmas Tanon Kabupaten Kediri - Faramista, Sukma; Pratamaningtyas, Susanti; Rahmaningtyas, Indah; Hardjito, Koekoeh (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
Nutrition of breastfeeding mothers is one of the success factors of exclusive breastfeeding. Breastfeeding mothers with inadequate nutrition will have an impact on milk production, resulting in exclusive breastfeeding rates in an area not reaching the standards set by the government. This study aims to determine the influence of environmental factors and the role of parents in selecting breastfeeding mothers' diets. The research design was cross-sectional, with a sample size of 134 respondents using a simple random sampling technique. The place of this study was in the Tanon Health Center Working Area which has 17 villages. Data were collected through questionnaires including the Eating Frequency Questionnaire, the Environmental Factor Questionnaire consisting of 13 questions, and the Parental Role Questionnaire consisting of 17 questions. Data processing techniques using the Contingency Correlation test with an α value of 0.05. The results of the study of environmental factors on food menu selection obtained a p-value of 0.002 Asymp. Sig (2-sided) <0.05, then H0 is rejected. The results of the analysis of the parental role factor in the selection of the breastfeeding mother's diet obtained a p-value of 0.001 Asymp. Sig (2-sided) <0.05, then H0 is rejected. So it can be concluded that there is an influence of environmental factors and the role of parents on the selection of diet of breastfeeding mothers in the Working Area of Tanon Health Center, Kediri Regency.